Enhanced nitrate removal in aquatic systems using biochar immobilized with algicidal Bacillus sp. AK3 and denitrifying Alcaligenes sp. M3: A synergistic approach - Khomsan Ruangrit; Kittiya Phinyo; Sahassawat Chailungka; Kritsana Duangjan; Apitchaya Naree; Jearanai Thasana; Wassana Kamopas; Senoch Seanpong; Jeeraporn Pekkoh; Nuttapol Noirungsee (PLoS ONE, 2025)
This study investigates the effectiveness of biochar immobilized with algicidal Bacillus sp. AK3 and denitrifying Alcaligenes sp. M3 in mitigating harmful algal blooms (HABs) and reducing nitrate pollution in aquatic environments. Over a six-day period, we analyzed changes in algal bloom-forming Microcystis density, chlorophyll-a levels (indicative of algal biomass), nitrate concentration, and microbial community composition in water treated with biochar and Bacillus sp. AK3 and Alcaligenes sp. M3-immobilized biochar. In water treatment using the AK3 and M3-immobilized biochar, Microcystis density decreased from 600,000 cells/mL to 80,000 cells/mL, and chlorophyll-a concentrations also substantially reduced, from 85.7 µg/L initially to 42.8 µg/L. Nitrate concentrations in the AK3 and M3-immobilized biochar treatment significantly decreased from approximately 23 mg/L to around 14 mg/L by Day 6, demonstrating the enhanced denitrification capabilities of the immobilized Alcaligenes sp. M3 and associated bacterial communities. The results also showed significant shifts in bacterial communities, with a decrease in Microcystis, highlighting the specific algicidal activity of Bacillus sp. AK3. The study underscores the potential of biochar-based treatments as a sustainable and effective approach for improving water quality and mitigating the environmental impacts of nutrient pollution and HABs.